A prospective trial comparing small bowel radiographs and video capsule endoscopy for suspected small bowel disease - Costamagna, Guido; Shah, Saumil K; Riccioni, Maria Elena; Foschia, Francesca; Mutignani, Massimiliano; Perri, Vincenzo; Vecchioli, Amorino; Brizi, Maria Gabriella; Picciocchi, Aurelio; Marano, Pasquale (Gastroenterology (New York, N.Y. 1943), 2002)
This study was undertaken to prospectively compare the clinical outcomes of small bowel radiographs with the wireless capsule endoscopy. Twenty-two patients were selected consecutively because of suspected small bowel disease. Two patients were excluded owing to ileal stenosis. Thus, the results of barium follow-through and the Given M2A wireless video capsule (Given Imaging Ltd., Yoqneam, Israel) endoscopy were compared in 20 patients (13 men; mean age, 52.5 yr; range, 29-78 yr). Barium follow-through was normal in 17 patients and showed ileal nodularity in 3 patients. Capsule endoscopy was normal in 3 patients and showed positive findings in the remaining 17 patients. The barium study was considered diagnostic in 4 (20%) patients. The capsule endoscopy was considered diagnostic in 9 (45%) patients, suspicious in 8 (40%) patients, and failed in 3 (15%) patients. For obscure gastrointestinal (GI) bleeding, the diagnostic potential of barium follow-through was much worse as compared with the capsule endoscopy (5% vs. 31%, P < 0.05). Capsule endoscopy was well tolerated and better accepted by patients when compared with the most recently performed endoscopic procedure. The video capsule endoscope was found to be superior to small bowel radiograph for evaluation of small bowel diseases. However, this novel wireless endoscope system needs further assessment because of limitations such as difficulties in interpretation of potentially nonspecific findings.